The Personalized System of Instruction: Review and Applications to Distance Education - Grant, Lyle K.; Spencer, Robert E. (International Review of Research in Open and Distributed Learning, 2003)
The present paper (a) outlines the basic features of the Personalized System of Instruction (PSI); (b) provides a brief history of PSI; and (c) describes the application of PSI to distance education. Some common misconceptions about PSI are also addressed. PSI is presented as a helpful universally applicable set of instructional practices that are well suited to distance teaching and learning.